SEJARAH KERAJINAN PANDAI BESI DI TANJUNG PINANG KECAMATAN TANJUNG BATU KABUPATEN OGAN ILIR SEBAGAI SUMBER PEMBELAJARAN SEJARAH - Suryani, Ida (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The formulation of the problem in this research is the historical value of what is available from the craft of blacksmith in Tanjung Pinang, Tanjung Batu Subdistrict, Ogan Ilir Regency which can be used as learning resource in class X SMA PGRI 2 Palembang. While the purpose of this study is to mengatahui historical value contained from the craft of a blacksmith in Tanjung Pinang Tanjung Batu District Ogan Ilir District that can be used as a source of learning history in class X SMA PGRI 2 Palembang. The method used in this research is descriptive qualitative method. Technique of collecting data that is, documentation, observation, interview. Techniques of data dashiness by means, source triangulation, triangulation techniques / methods and triangulation theory. Data analysis technique used in this research is data analysis technique of data analysis used in this research is interactive analysis analysis technique with some component such as data collection, data reduction, data presentation and conclusion. Based on the results of data analysis and discussion that has been done in this study the history of SMA PGRI 2 Palembang teachers do not know the area of Tanjung Pinang village has a cultural heritage of karajinan blacksmith. Blacksmith skill is a cultural heritage of the ancestral heritage that until now still preserved by the community of Tanjung Pinang village that can be used as a source of learning history in the class X SMA PGRI 2 Palembang. With the history of this blacksmith craft adds knowledge of the teacher to the area that has cultural results. Keywords: History of Blacksmith, History Learning Resources